Factors Affecting the Strength of a Young Family - Inagamova Feruza Khurshitovna (Genius Journals, 2023)
Values and their meeting in transformational processes under the influence of various social factors in the life of everymember of the society, in turn, affect various social units and groups within this cociety, especially the family institution.
Keywords: Person; family; transformation of values; values